Pseudoazurin from Sinorhizobium meliloti as an electron donor to copper-containing nitrite reductase: influence of the redox partner on the reduction potentials of the enzyme copper centers - Ferroni, Felix Martín (2014)
Pseudoazurin (Paz) is the physiological electron donor to copper-containing nitrite reductase (Nir), which catalyzes the reduction of NO2− to NO. The Nir reaction mechanism involves the reduction of the type 1 (T1) copper electron transfer center by the external physiological electron donor, intramolecular electron transfer from the T1 copper center to the T2 copper center, and nitrite reduction at the type 2 (T2) copper catalytic center. We report the cloning, expression, and characterization of Paz from Sinorhizobium meliloti 2011 (SmPaz), the ability of SmPaz to act as an electron donor partner of S. meliloti 2011 Nir (SmNir), and the redox properties of the metal centers involved in the electron transfer chain. Gel filtration chromatography and sodium dodecyl sulfate–polyacrylamide gel electrophoresis together with UV–vis and EPR spectroscopies revealed that as-purified SmPaz is a mononuclear copper-containing protein that has a T1 copper site in a highly distorted tetrahedral geometry. The SmPaz/SmNir interaction investigated electrochemically showed that SmPaz serves as an efficient electron donor to SmNir. The formal reduction potentials of the T1 copper center in SmPaz and the T1 and T2 copper centers in SmNir, evaluated by cyclic voltammetry and by UV-vis- and EPR-mediated potentiometric titrations, are against an efficient Paz T1 center to Nir T1 center to Nir T2 center electron transfer. EPR experiments proved that as a result of the SmPaz/SmNir interaction in the presence of nitrite, the order of the reduction potentials of SmNir reversed, in line with T1 center to T2 center electron transfer being thermodynamically more favorable.